PUBLICATIONS OF THE WEEK. (Bookseller, 2005)
The article presents information on various newly published books. Books are presented in various categories like agriculture, anthropology, antique furniture, air transport, aircraft, architecture and town planning, art, and general. Some of the books listed are "African Archaeology," by D.W. Phillipson; "Planning and Surveying"; " Work Place City: Perspectives of an Urban Redevelopment Culture"; "Business Jets Quick Reference"; "Mutants: On the Form, Varieties and Errors of the Human Body," by Armand Marie Leroi; "Sutton Hoo: A Seventh-Century Princely Burial Ground and Its Context," by Martin Carver; among others.